Top-down modulation of the auditory steady-state response in a task-switch paradigm - Müller, Nadia; Schlee, Winfried; Hartmann, Thomas; Lorenz, Isabel; Weisz, Nathan (Frontiers in Human Neuroscience, 2009)
Auditory selective attention is an important mechanism for top-down selection of the vast amount of auditory information our perceptual system is exposed to. In the present study, the impact of attention on auditory steady-state responses - previously shown to be generated in primary auditory regions - was investigated. This issue is still a matter of debate and recent findings point to a complex pattern of attentional effects on the aSSR. The present study aimed at shedding light on the involvement of ipsilateral and contralateral activations to the attended sound taking into account hemispheric differences and a possible dependency on modulation frequency. In aid of this, a dichotic listening experiment was designed using amplitude-modulated tones that were presented to the left and right ear simultaneously. Participants had to detect target tones in a cued ear while their brain activity was assessed using MEG. Thereby, a modulation of the aSSR by attention could be revealed, interestingly restricted to the left hemisphere and 20 Hz responses: Contralateral activations were enhanced while ipsilateral activations turned out to be reduced. Thus, our findings support and extend recent findings, showing that auditory attention can influence the aSSR, but only under specific circumstances and in a complex pattern regarding the different effects for ipsilateral and contralateral activations.